Evaluation of the change six minute walking test distance with conditioning - Tarik, Kivrak; Smail, Idot Korkmaz; Mehdi, Karasu; Ozkan, Karaca; Kobat, M. A.; Yilmaz, M. B. (Wiley, 2020)
[Abstract Not Available]